Molecular fingerprinting of bovine mastitis-associated Staphylococcus aureus isolates from India - Madhavi Annamanedi (Nature Portfolio, 2021)
Abstract Staphylococcus aureus is a major etiological agent of clinical and subclinical bovine mastitis. Owing to the mostly backyard dairy practices, we hypothesized that genetic diversity among mastitis-associated S. aureus from India would be high, and investigated 166 isolates obtained mostly from the Southern State of Karnataka, but also from a few other states. The results revealed (a) 8 to 13 fragments in pulsed-field gel electrophoresis (PFGE), forming 31 distinct patterns, and (b) 34 spa types, of which three (t17680, t18314, and t18320) were newly identified. Multi-locus sequencing typing (MLST) identified 39 sequence types (STs), with ST2454 (34.4%) and ST2459 (24%) being the most commonly represented, which clustered to clonal complexes (CC) CC9 and CC97, respectively; 12 STs were newly identified. Thirty-four (20.5%) of the 166 isolates displayed oxacillin resistance. On the other hand, whereas none were mecC+, 44 (26.5%) isolates were mecA+, with a predominance of SCCmecIVb (26/32 isolates, others being untypeable); 24 isolates (14.46%) were oxacillin-susceptible methicillin-resistant S. aureus (OS-MRSA; mecA+ but OS). Integrated analysis revealed that CC9-ST2454- and CC97-ST2459-SCCmecIVb were the predominant MRSA, although the distribution of CC9 and CC97 was similar between methicillin-resistant and -susceptible isolates. By PCR, 56.25%, 28.75% and 47.5% of the 166 isolates were positive for hlg, tsst and pvl genes, respectively. Our results, for the first time describe the application of a combination of various molecular methods to bovine mastitis-associated S. aureus isolates from India, corroborate the worldwide distribution of CC97 and CC9, and suggest pathogenic potential of the isolates.